PENGARUH GERAKAN LITERASI DALAM MENINGKATKAN MINAT BACA SISWA - Irvan Sutrisna; Septina Sriwulan; Via Nugraha (IKIP Siliwangi, 2019)
In Indonesia, the interest in reading in all circles is still lacking, especially students and students who are usually involved in the world of education. Because people who are less aware of the benefits of literacy. In addition, there are quite a lot of obstacles that occur when reading. When the government makes a policy to build a culture of literacy through ways of getting students to read for 10-15 minutes before learning begins. This study intends to determine the influence and obstacles of the School Literacy Movement (GLS) program on reading hobbies among students at the Assyukur Bakti Health Vocational School. The subjects in this study were students of Assyukur Bakti Health Vocational School. The formulation of the problem in this study are: 1) What is meant by literacy? 2) What are the obstacles in literacy? 3) The approach used in this study is qualitative research. The data collection technique is done by questionnaire, observation, documentation, and interviews. The results of the study found that students' fondness for reading increased can be seen from the results of the questionnaire which showed the results that the students of reading were reading as gifts after the School Literacy Movement. Literacy culture can be improved, their reading activities can be observed, and their reading skills develop well by cultivating a culture of literacy in students.